,,O zaświatowym buncie i o opętaniu Adama-Ducha...”. Antropologia neognostycka Jakuba Boehmego a III część Dziadów - Fedorowicz, Katarzyna (Slavia Occidentalis, 2014)
This article develops Rafał Marceli Blüth’s thesis about influence of Jakob Boehme’s conception on anthropological vision contained in III part of Dziady. The demise of Mickiewicz’s Konrad is proceeding in similar manner to Adam in terms of neognostic from Zgorzelec. Problem of will and human participation in divinity and against the divinity’s realization in history presented in literary work corresponds with author of Aurora’s visions. Futhermore, imitation Christi makes a condition of man’s salvation and most likely poses a crucial problem for philosophical reconstruction of messianic vision contained in Mickiewicz’s literary work. Moreover, it is possible to indicate on number of locus communis of Boehme’s theory and represented world in III part of Dziady.